IMPLEMENTING CORPUS-BASED LEARNING TO IMPROVE VOCABULARY ACQUISITION IN ESL/EFL CONTEXTS - Muedinova Liana Elvirovna; Radjabova Gulnoza Giyosiddinovna (Bright Mind Publishing, 2025)
The article examines the incorporation of corpora in vocabulary teaching in contemporary language education. By looking at prominent examples such as the Wellington and Kolhapur Corpora, the study addresses the difficulties teachers encounter in implementing authentic language data while highlighting the value of digital tools in engaging students and improving their language comprehension. It offers suggestions for focused instruction and suitable corpus selection, highlighting the potential of corpora to enhance vocabulary learning and enhance overall language proficiency.
Keywords: Technology, corpus, structure, methodology, vocabulary, benefits, drawbacks, conventional materials, classroom.